Severe Metabolic Acidosis: A Case of Triple Hit with Ketogenic Diet, Vinegar, and Metformin in an Obese Patient. (15th September 2020) - Rana, Abdul Mughees; Mansoor, Kannan; Assad, Salman; Abouzid, Mahmoud; Ogu, Iheanyichukwu; Bandak, Ghassan Salim Issa
Abstract : Obesity is an epidemic with high burden of disease. It is directly proportional to increased risk of morbidity and mortality. Ketogenic diet and herbal supplements have recently gained popularity amongst patients struggling with weight loss. There are limited data available for most of these supplements contrary to the claims laid by the mainstream media. Due to lack of awareness, this patient population is at high risk of adverse effects. We present a case of severe acidosis secondary to ketogenic diet and acetic acid (vinegar) ingestion. The use of dietary acetic acid is usually well tolerated; however, in this case, the large quantities and presence of acute renal injury may have worsened the acidosis. Severe ketosis in setting of ketogenic diets is a serious complication, which is infrequently reported in literature. Many of these diets and supplements may seem harmless, but as our case illustrates, when combined with other risk factors, patients can face adverse effects and even hospitalization. It is imperative that such dietary practices are physician supervised to avoid complications. With the recent surge of over-the-counter weight loss supplements and fat diets, physicians need to engage in dietary discussion with patients when attempting to lose weight.